“An A is an A?” Maybe in North America, but less so elsewhere - Martin R. W. Hiebl (European Management Review, 2023)
With reference to recent debate about the increasing “an A is an A” mentality at business schools, I provide evidence on the prevalence of this mentality in North America versus other regions of the world (RoW). The evidence presented is derived from the data selection procedures employed in conducting systematic reviews of management research because a focus on specific journals in this selection can be seen as an artifact of the “an A is an A” mentality. My findings suggest that this mindset is more widespread in North American business schools and less so elsewhere. This implies that in order to find remedies against the detrimental effects of the “an A is an A” mentality, North American business school leaders and academics might find inspiration in other countries. In addition, I suggest that a part of the solution could also be directing PhD students toward a more inclusive selection of journals and articles in reviews of management research.
Keywords: 650; business schools; journal rankings; performance management; regional differences; systematic reviews; universities